Individualization of Exertion while Monitoring Functional State during Exercising (Baltic Journal of Sport and Health Sciences, 2016)
Background. Individualization in workloads is important in order to get optimal benefits from exercising and long-term adaptation. Heart rate (HR) monitoring during exercise can be valuable for the feedback formation. The aim of the study was to compare the calculated HR values recommended for individualization of endurance training workloads while taking into account the HR at real or relative rest.Methods. The participating 76 healthy adults were asked to measure the pulse rate, i.e. HR self-examination at absolute and relative rest states. The results obtained during the study were analysed according to the age and gender by calculating HR Reserve  and the recommended intensity of exercising at 50% of HR Reserve ; 70% of HR Reserve ; 85% of HR Reserve .Results. Significant difference was found when comparing the averaged values of HR obtained at the real and relative states and even greater difference was observed between relative and real resting conditions in younger groups. When calculating the recommended HR values for exercising intensity, recommended HR values significantly differ depending on whether the real or relative rest states were taken into account.  This means that the algorithm for feedback formation should take into account the initial values of HR corresponding to the state of absolute rest, i.e. after 8 hours of sleep.Conclusion. The HR at relative rest state is different to the real rest state HR and therefore the algorithm for feedback formation should take into account this difference, i.e. the corresponding correction of such HR meanings should be installed.Keywords:  health promotion, cardiovascular system, individualization.